A Validated Liquid Chromatographic Method for the Estimation of Imatinib Mesylate in Dosage Forms: Application to Chemometrics based Robustness Testing and Greenness Assessment - Panda, S.S.; Mohanty, S.K.; Pulusu, V.S.; Sahu, S.; Das, B. (Asian Journal of Chemistry, 2023)
An eco-friendly liquid chromatography method was developed for determining imatinib mesylate in pharmaceuticals. During pre-development studies, Using a greener mobile phase and a combination of qualitative and semi-quantitative green metrics techniques, the environmental sustainability of the procedure was maintained. Methanol:water (pH maintained at 3.5 using orthophosphoric acid) at 75:25%, v/v flowing at 1 mL/min was the final mobile phase used on a C-18 column. The diode array detector detected imatinib at 262 nm. Method specificity, accuracy, precision, selectivity and system suitability were tested over a linear concentration range of 5-120 μg/mL of imatinib. The limit of detection and limit of quantitation values were 1.5 and 5.0 μg/mL, respectively. In addition, the factorial design showed the procedure to be reliable with minimum testing. Finally, the method recovered the maximum (> 99%) of the analyte from the dosage form. Overall, the present method is suitable for routine applications in quality control of dosage forms of imatinib.